(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2022)
Badut Temple is the oldest temple on Java Island and a historical relic of the Kanjuruhan Kingdom that collapsed due to natural and human factors. Therefore, this study aims to determine the suitability of the Badut Temple design drawn by B. De Haan. Based on the vastu purusha mandala philosophy, this Hindu-style temple uses repeated divisions of squares to prove that the design of the head of the temple uses Fractal Geometry with the box-counting method. The results showed that the fractal dimension index on the foot, body, and head with a ratio of 1.878: 1.870: 1.872 or be rounded up to 1:1:1. This means that the B. De Haan sketch design is similar to the existing temple. Furthermore, the ratio of the height of the foot, body, and head was 2.35:4.88:6.94 which is simplified to 1:2:3. Therefore, the Badut Temple adheres to the Vastu Purusha Mandala philosophy.